Does acute weight loss and gain affect hydration status in adolescent wrestlers? - Demirkan, E.; Avci, E.; Gargi, R. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: The rapid weight loss and gain is a common practice in wrestlers within a week before competition. The aim of this study was the effects of rapid weight loss and gain before official weigh-in, along with during the competition in adolescent wrestlers.